Complex Raynaud's phenomenon: evolving concepts of management. (December 2013) - Meier, Florian MP; Frerix, Marc; Müller-Ladner, Ulf
Raynaud's phenomenon (RP) can occur as benign, usually primary, RP. By contrast, complex RP is mainly secondary and can be caused by severe, chronic diseases such as systemic sclerosis. This article mainly reviews treatment opportunities for secondary RP, but also refers to primary RP wherever evidence is at hand. The main focus is on drugs recommended by expert panels or research consortia, such as the European League Against Rheumatism Scleroderma Trials and Research (EUSTAR) group. In addition, this review intends to provide a comprehensive overview of the different therapeutic approaches that have been tested in RP to date, some with more impact versus others with less impact. Thereby, conclusions about the pathogenesis of RP can be drawn, which can guide future clinical trials and research.